2020
DOI: 10.1088/1742-6596/1700/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Training Kit For Basic Electronic Control on Automotive Field

Abstract: This study aims to determine: (1) the material needed by students in the Basic Practice of Electronic Control Systems in the automotive field, (2) the design of the Basic Electronic Control System Training Kit in the automotive field, (3) the results of the development of the Basic Electronic Control System training kit in the automotive field., (4) eligibility of the basic training kit for the Electronic Control System in the automotive sector, and (5) users responses to the development results of the Basic E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…This finding is consistent with previous research showing the beneficial effects of tailor-made training aids for the learning process on student aptitude [4]. Even though some research indicated a moderate impact, the aggregate results nonetheless demonstrated the advantages of raising pupils' skill levels [13], [14], [30]. Research in the field of EMC has been done a lot before.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with previous research showing the beneficial effects of tailor-made training aids for the learning process on student aptitude [4]. Even though some research indicated a moderate impact, the aggregate results nonetheless demonstrated the advantages of raising pupils' skill levels [13], [14], [30]. Research in the field of EMC has been done a lot before.…”
Section: Discussionsupporting
confidence: 90%
“…Untuk penyiapan proses belajar mengajar dengan pendekatan blended learning ini diperlukan perangkat pembelajaran salah satunya Learining Kit. Learning Kit adalah kumpulan beberapa bahan ajar atau alat bantu pembelajaran baik secara individuu atau pun kolaboratif dalam bentuk teks, diagram, foto, grafik, maupun video (Tafakur, Sukaswanto, Solikin & Wardani, 2020). Salah satu tujuan dari learning kit adalah untuk meneliti bagaimana siswa atau mahasiswa mengadopsi dan menyesuaikan strategi untuk pembelajaran individu dan kelompok, dapat menguraikan seberapa baik siswa atau mahasiswa belajar serta membantu menguasai setiap materi atau tugas yang diberikan (Winne, Hadwin, & Gress, 2010).…”
Section: Pendahuluanunclassified